2021
DOI: 10.1155/2021/5590109
|View full text |Cite
|
Sign up to set email alerts
|

Laser Vaporization of Intracoronary Thrombus and Identifying Plaque Morphology in ST-Segment Elevation Myocardial Infarction as Assessed by Optical Coherence Tomography

Abstract: Objectives. We evaluated the thrombus-vaporizing effect of excimer laser coronary angioplasty (ELCA) in patients with ST-segment elevation myocardial infarction (STEMI) by optical coherence tomography (OCT). Background. Larger intracoronary thrombus elevates the risk of interventional treatment and mortality in patients with STEMI. Methods. A total of 92 patients with STEMI who presented within 24 hours from the onset and underwent ELCA following manual aspiration thrombectomy (MT) were analyzed. Results. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, a post-DCB CAG revealed another ISR despite being symptom-free. Nevertheless, it should be noted that the damage to the coronary intima associated with ELCA might contribute to stent thrombosis and restenosis [ 40 ]. Therefore, despite the potential feasibility of ELCA in TAK with CA involvements, the conservation of coronary intima during ELCA is critical to preventing ISR in the long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, a post-DCB CAG revealed another ISR despite being symptom-free. Nevertheless, it should be noted that the damage to the coronary intima associated with ELCA might contribute to stent thrombosis and restenosis [ 40 ]. Therefore, despite the potential feasibility of ELCA in TAK with CA involvements, the conservation of coronary intima during ELCA is critical to preventing ISR in the long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of ELCA in primary PCI for STEMI has not been conclusively proven in a prospective manner, and there are no recommendations in the current guidelines. Although smaller observational studies and case reports have suggested the efficacy of ELCA during primary PCI, 20,[24][25][26] systematic proof of its clinical benefits has not been reported. The present study, which included a substantial number of primary PCI cases using ELCA, failed to show a clinical benefit of ELCA, suggesting that the routine use of ELCA might not be effective for primary PCI.…”
Section: Future Perspectivementioning
confidence: 99%
“…1C) (18). In the present study, the culprit lesion was categorized into plaque rupture, plaque erosion or calcified nodule (19). Plaque rupture was defined as the presence of fibrous cap discontinuity and cavity formation in the plaque (Fig.…”
Section: Data Collectionmentioning
confidence: 99%